Carbonaceous and phosphate-rich sediments of the Miocene Monterey Formation at El Capitan State Beach, California, USA - John, Cédric M; Föllmi, Karl B.; De Kaenel, Eric; Adatte, Thierry; Steinmann, Philipp; Badertscher, Christophe (My University, 2002)
The organic- and phosphate-rich interval of the Monterey Formation at El Capitan State Beach (west of Santa Barbara, California, U.S.A.; late early to early late Miocene in age) is composed of a carbonaceous marl (TOC contents between 1.2 and 23.2 wt %) with intercalated phosphate-rich laminae, lenses, and layers. Subordinate lithologies include ash layers, dolomitized horizons, and siliceous beds. We distinguished five lithological units: (1) a gray marl unit lacking major phosphate accumulations (> 16.3 Ma; average TOC content 2% by weight; average sedimentation rate 75 m/My; average TOC accumulation rate 0.19 mg/cm(2)/yr); (2) a black marl unit including light-colored phosphatic laminae, lenses, and discrete particles (16.3-14.5 Ma; average TOC content 7.5% by weight; average sedimentation rate 20 m/My; average TOC accumulation rate 0.19 mg/cm(2)/yr); (3) a red marl unit including light-colored phosphatic laminae, lenses, and commonly reworked particles (14.5-12.7 Ma; average TOC content 15% by weight; average sedimentation rate 20 m/My (14.5-13.3 Ma) and 2 m/My (13.3-12.7 Ma), respectively; average TOC accumulation rate 0.39 mg/cm(2)/yr (14.5-13.3 Ma) and 0.04 mg/cm(2)/yr (13.3-12.7 Ma), respectively); (4) a unit of complex and condensed phosphatic beds, interbedded with red marl (12.7-10.8 Ma; average sedimentation rate 3 m/My); and (5) a black marl unit with intercalated phosphatic laminae and lenses (< 10.8 Ma; average sedimentation rate 9 m/My; average TOC accumulation rate 0.09 mg/cm(2)/yr). Phosphogenesis and accumulation of phosphate were dynamic processes, which started with local phosphogenesis leading to the formation of phosphatized particles, as well as stratigraphically bound phosphogenesis leading to the formation of phosphate laminae and lenses. Phases of subsequent sediment reworking resulted in the concentration of phosphate particles in phosphate-rich layers, and repeated phases of sediment reworking and phosphogenesis ultimately resulted in the formation of the complex phosphate condensed horizons. Preservation of organic matter was favored by high productivity rates and by the development of dysaerobic bottom-water conditions. The dynamic sedimentary environment likely led to the formation of early diagenetic phosphatic lids (which may have sealed off subjacent organic-rich layers) as well as to the rapid deposition of entire layers in the form of mud flows, thereby eventually enhancing the potential of organic-matter preservation. Our new age data suggest that at the El Capitan State Beach section the intervals characterized by high TOC values and maximum TOC accumulation rates (red marl), as well as significant quantities of in situ phosphates appeared in the late middle Miocene, i.e., during and after the major cooling phase at around 14.5 Ma. This implies that deposition of phosphate and organic carbon continued well after this cooling phase, thereby underlining the observation that preservation of organic carbon in the Monterey Formation is not only dependent on climate change during the mid Miocene but also on regional conditions.
Keywords: LAMINATED DIATOMACEOUS SEDIMENTS; MIDDLE; DEPOSITS; CLIMATE; STRATIGRAPHY; TRANSITION; PACIFIC; SECTION; OXYGEN; BEDS